Molecular structure analysis of ascending aorta aneurysm upon atherosclerosis. (25th November 2020) - Mamarelis, I; Mamareli, V; Kyriakidou, M; Tanis, O; Mamareli, C; Kotoulas, S; Subramaniyan Parimalam, S; Packirisamy, M; Badilescu, S; Anastassopoulou, J; Kotoulas, C; Theophanides, T
Abstract: Background: The atherosclerotic ascending aorta could represent a potential source of emboli or could be an indicator of atherosclerosis in general with high mortality. The mechanism of aneurysm formation and atherosclerosis of the ascending aorta at the molecular level has not yet been clarified. To approach the mechanism of ascending aortic lesions and mineralization at a molecular level, we used the non-destructive FT-IR, Raman spectroscopy, SEM and Hypermicroscope. Methods: Six ascending aorta biopsies were obtained from patients who underwent aortic valve replacement (AVR) cardiac surgery. CytoViva (einst inc) hyperspectral microscope was used to obtain the images of ascending aorta. The samples were dissolved in hexane on a microscope glass plate. The FT-IR and Raman spectra were recorded with Nicolet 6700 thermoshintific and micro-Raman Reinshaw (785nm, 145 mwatt), respectively. The architecture of ascending aorta biopsies was obtained by using scanning electron microscope (SEM of Fei Co) without any coating. Results: FT-IR and Raman spectra showed changes arising from the increasing of lipophilic environment and aggregate formation (Fig. 1). The band at 1744 cm –1 is attributed to aldehyde CHO mode due to oxidation of lipids. The shifts of the bands of the amide I and amide II bands to lower are associated with protein damage, in agreement with SEM data. The bands at about 1170–1000 cm –1 resulted from the C-O-C of advanced glycation products as result of connecting tissues fragmentations and polymerization. The spectroscopic data were analogous with the lesions observed with SEM and hypermicroscopic images. Conclusions: The present innovate molecular structure analysis showed that upon ascending aorta aneurysm development an excess of lipophilic aggregate formation and protein lesions, changing the elasticity of the aorta's wall. The released Ca2+ interacted mostly with carbonate-terminal of cellular protein chains accelerated the ascending aorta calcifications. Funding Acknowledgement: Type of funding source: None